Long Term Remission and Cardiac Toxicity of a Combination of Ipilimumab and Nivolumab in a Patient With Metastatic Head and Neck Carcinoma After Progression Following Nivolumab Monotherapy - Schwab, Katjana S.; Kristiansen, Glen; Isaak, Alexander; Held, Stefanie E. A.; Heine, Annekristin; Brossart, Peter (Frontiers in Oncology, 2019)
Management of patients with metastatic squamous cell cancer of the head and neck, refractory to initial therapy with standard chemo- and radiation protocols, remains difficult with poor overall prognosis and limited therapeutic options. Nivolumab (a programmed death receptor-1 ,PD-1 blocking antibody) has been approved in Germany since June 2017 for the treatment of squamous cell carcinoma of the head and neck in adults. Nivolumab in combination with Ipilimumab (an anti-CTLA 4 antibody) is licenced in the EU for the treatment of advanced (unresectable or metastatic) melanoma in adults. In April 2018, the Food and Drug Administration granted approvals to nivolumab and Ipilimumab in combination for the treatment of intermediate or poor risk, previously untreated advanced renal cell carcinoma. So far, there are no clinical data on the therapeutic efficacy of nivolumab in combination with ipilimumab in squamous cell cancer of the head and neck. This report is about a patient with metastastic squamous cell cancer of the head and neck refractory to nivolumab monotherapy, who showed a remarkable response to combination therapy with nivolumab and ipilimumab over a period of 2 years, but developed serious renal failure and a Takotsubo cardiomyopathy.